Understanding Toxic Leadership: The role of Job Stress and Job Satisfaction in Mediating Turnover Intention - Djatmiko Noviantoro; Septiana Septiana; Sari Sakarina (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to examine the mediating effects of work stress and job satisfaction on the relationship between toxic leadership and turnover intention. The high level of turnover intention, along with its potential to undermine organizational stability and productivity, has become a serious concern for academics and practitioners. This research employs a quantitative approach using path analysis and Structural Equation Modeling with a sample of 126 respondents from the Sumatra Retail Frontliner and Sales Division using purposive sampling. Organizational Behavior theory is utilized to discuss various factors influencing employee behavior, including turnover intention. The study reveals both direct and indirect effects of toxic leadership on turnover intention through the mediation of work stress and job satisfaction. Consequently, partial mediation is concluded for all mediating variables. This study is limited by the scope and timeframe, which could be expanded in future research. Further studies are encouraged to develop and enhance research models, particularly focusing on leadership training aimed at fostering more adaptive leadership styles. This research contributes to understanding the impact of toxic leadership on turnover intention by highlighting the mediating roles of work stress and job satisfaction.